Front cover: Diet during Pregnancy is Implicated in the Regulation of Hypothalamic RNA Methylation and Risk of Obesity in Offspring. Issue 14 (23rd July 2018) - Kaspi, Antony; Khurana, Ishant; Ziemann, Mark; Connor, Timothy; Spolding, Briana; Zimmet, Paul; Walder, Ken; El‐Osta, Assam
Abstract : Mol. Nutr. Food Res. 2018, 62, 1800134 DOI:10.1002/mnfr.201800134 Parental diet restriction regulates hypothalamic DNA cytosine methylation (5mC) and RNA adenosine methylation (m6A) and the risk of obesity in offspring. Parental diet alters hypothalamic appetite signals that coordinate epigenetic changes regulating the expression of genes implicated in obesity. Further details about this study can be found in article number1800134 by Assam El‐Osta and co‐workers.